2015
DOI: 10.1007/s11695-015-1956-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Race, and the Quality of Life Factors Most Important to Patients’ Well-Being Among Those Seeking Bariatric Surgery

Abstract: Background Evidence suggests obesity-related social stigma and impairment in work function may be the two most detrimental quality of life (QOL) factors to overall well-being among patients seeking weight loss surgery (WLS); whether the relative importance of QOL factors varies across patient sex and race/ethnicity is unclear. Methods We interviewed 574 patients seeking WLS at two centers. We measured patient’s health utility (preference-based well-being measure) as determined via standard gamble scenarios a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The authors suspected that men tend to seek treatment later [132]. This fits with the results of Wee et al, who found differences concerning self-evaluated quality of life, social stigma, and the utility of bariatric surgery in achieving personal goals depending on sex as well as ethnicity [134].…”
Section: Metabolism Outcome and Quality Of Lifesupporting
confidence: 72%
“…The authors suspected that men tend to seek treatment later [132]. This fits with the results of Wee et al, who found differences concerning self-evaluated quality of life, social stigma, and the utility of bariatric surgery in achieving personal goals depending on sex as well as ethnicity [134].…”
Section: Metabolism Outcome and Quality Of Lifesupporting
confidence: 72%
“…16 Similarly, Wee's secondary analysis of patients with severe obesity found that males pursued bariatric surgery due to experiencing weight stigma. 9 However, no single-gender study of men with severe obesity describes improving psychological health as a motivator for seeking bariatric surgery. Improving body image is less common as a motivator for patients seeking MWM in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…5 Two mixed-gender studies noted that functionality was a motivator for participants with obesity and severe obesity pursuing bariatric surgery. 8,9 In particular, Wee found that males were motivated by poor physical functioning. 9 Our study supports existing mixed-gender literature suggesting that patients were motivated to pursue surgery to prevent death or extend their lifespan.…”
Section: Motivations Of Males With Severe Obesitymentioning
confidence: 99%
See 2 more Smart Citations